1990
DOI: 10.1099/00221287-136-10-2067
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance spectroscopic investigation of the inhibition of the phosphoroclastic system of Clostridium sporogenes by nitrite

Abstract: The proposal that nitrite exerts its inhibitory effect on anaerobic bacteria by direct interaction with the ironsulphur proteins of the phosphoroclastic system was investigated. The effects of nitrate, nitrite with or without ascorbate, and nitric oxide on the growth of Clostridium sprogenes in liquid cultures at pH 7.4, on the rates of hydrogen production, and on the activities of the enzymes pyruvate-ferredoxin oxidoreductase and hydrogenase, and of ferredoxin were investigated. In agreement with previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Carpenter et al (9) also reported the loss of activity of ferredoxin and pyruvate-ferredoxin oxidoreductase during treatment with nitrite. However, Payne et al (25,26) examined the effect of nitrite and iron-sulfur-nitrosyl complexes on ironsulfur clusters in Clostridium sporogenes cells (25) and on the isolated iron-sulfur proteins (26) and were unable to demonstrate a direct action of the compounds on the iron-sulfur proteins. A second possible effect is that of a general oxidizing agent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carpenter et al (9) also reported the loss of activity of ferredoxin and pyruvate-ferredoxin oxidoreductase during treatment with nitrite. However, Payne et al (25,26) examined the effect of nitrite and iron-sulfur-nitrosyl complexes on ironsulfur clusters in Clostridium sporogenes cells (25) and on the isolated iron-sulfur proteins (26) and were unable to demonstrate a direct action of the compounds on the iron-sulfur proteins. A second possible effect is that of a general oxidizing agent.…”
mentioning
confidence: 99%
“…Chemical determination of the sulfhydryl groups in cell fractions was used to assess the effect of SNP on the -SH content of each fraction. Electron paramagnetic resonance (EPR) spectroscopy of whole cells and cell fractions was used to observe the quantities of iron-sulfur proteins and their redox state in the cells (25). EPR signals were also detected from various species formed by reduction of the nitroprusside ion.…”
mentioning
confidence: 99%
“…The favoured chemistry of this highly reactive nitrosonium cation species is characterised by addition and substitution reactions with nucleophiles (electron‐rich bases and aromatics). At pH 7, nitrite is a rather ineffective nitrosylating agent (only 0.022% present as HNO 2 ); increased protonation (at pH 3.4 in the experiments described here) increase its effectiveness [23]. S ‐Nitrosothiols predominate over other reaction products under physiological conditions [24].…”
Section: Discussionmentioning
confidence: 79%
“…This ‘phosphoroclastic’ system in C. sporogenes and C. botulinum is inhibited (Woods et al . 1981; Payne et al . 1990) and growth of the organisms is arrested (Duncan and Foster 1968) by concentrations in the mM range.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the oxidation of pyruvate to acetate and H 2 in both types of organisms requires pyruvate: ferredoxin oxidoreductase, ferredoxin and hydrogenase. This ÔphosphoroclasticÕ system in C. sporogenes and C. botulinum is inhibited (Woods et al 1981;Payne et al 1990) and growth of the organisms is arrested (Duncan and Foster 1968) by NO À 2 concentrations in the mM range. Interest in the cytotoxic effects of nitrosylating reagents and NO has become intense, as macrophages produce these agents to kill parasites (Fernandes and Assreuy 1997).…”
Section: Introductionmentioning
confidence: 99%